Anthocyanin Stability Profile of Mango Powder: Temperature, pH, Light, Solvent and Sugar Content Effects - Shireen Akther; Farhana Sultana; Md. Rahim Badsha; Jakia Sultana Jothi; Md. Abdul Alim (Turkish Journal of Agriculture: Food Science and Technology)
Anthocyanins, a major natural food colorant rich in mango powder, need considerable protection during processing and storage for better retention due to colour instability. The purpose of the study is to evaluate the stability of the anthocyanin’s extracts obtained from cabinet dried mango powder under different factors which could disrupted the anthocyanin pigments during processing. The factors are processing temperature and time (30°C, 60°C and 80°C for 10, 20 and 30 minutes each, respectively), storage conditions (room temperature, refrigerator temperature and freezing temperature), pH (2, 3, 4, 7 and 10), oxygen, influence of light, different extraction solvent (methanol, absolute ethanol, acidified ethanol (1%), and 50% KMS -Ethanol), sugar level (20%, 40%, and 60%). The intensity of the extracted colour was measured at wavelength 520 nm using UV-VIS spectrophotometer. The results can elucidate the increasing heating temperature and time, sugar content, and exposure to light is able to spoil the anthocyanin molecule. There was a proportional effect of pH and oxygen. The anthocyanin stability was found better in pH=10, acidified ethanol (1%) as extracting solvents, absence of light as processing condition and refrigeration temperature as storage temperature. Hence, these findings could be useful in the food industry to choose a proper processing condition for development of mango powders-based products for satisfying the consumer perception by retaining anthocyanin pigment.